2017
DOI: 10.1186/s12902-017-0194-2
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid receptor blockade reduces alanine aminotransferase in polycystic ovary syndrome independent of weight loss

Abstract: BackgroundEvidence suggests that endocannabinoid system activation through the cannabinoid receptor 1 (CB1) is associated with enhanced liver injury, and CB1 antagonism may be beneficial. The aim of this study was to determine the impact of rimonabant (CB1 antagonist) on alanine aminotransferase (ALT), a hepatocellular injury marker, and a hepatic inflammatory cytokine profile.MethodsPost hoc review of 2 studies involving 50 obese women with PCOS and well matched for weight, randomised to weight reducing thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…20 The 3 agents induced comparable reductions in the free androgen index but none affected the lipid profi le. 20 Pioglitazone also reduced high-sensitivity C-reactive protein (hs-CRP) levels, a marker of subclinical infl ammation and increased cardiovascular risk 21 , whereas orlistat and metformin had no effect 20 . In a more recent large randomized study (n = 149), orlistat combined with lifestyle modifi cation (caloric restriction and increased physical activity) for 16 weeks induced similar reductions in weight with orlistat and lifestyle modifi cation combined with oral contraceptive pills (OCP, ethinyl estradiol 20 mcg/1 mg norethindrone acetate) and greater than OCP alone (6.2, 6.4 and 1.0%, respectively).…”
Section: Orlistatmentioning
confidence: 95%
See 2 more Smart Citations
“…20 The 3 agents induced comparable reductions in the free androgen index but none affected the lipid profi le. 20 Pioglitazone also reduced high-sensitivity C-reactive protein (hs-CRP) levels, a marker of subclinical infl ammation and increased cardiovascular risk 21 , whereas orlistat and metformin had no effect 20 . In a more recent large randomized study (n = 149), orlistat combined with lifestyle modifi cation (caloric restriction and increased physical activity) for 16 weeks induced similar reductions in weight with orlistat and lifestyle modifi cation combined with oral contraceptive pills (OCP, ethinyl estradiol 20 mcg/1 mg norethindrone acetate) and greater than OCP alone (6.2, 6.4 and 1.0%, respectively).…”
Section: Orlistatmentioning
confidence: 95%
“…19 In a post-hoc analysis of 2 randomized studies (n = 50), orlistat 120 mg tid reduced weight by 5.7% whereas metformin 500 mg tid and pioglitazone 45 mg od had no effect. 20 Orlistat and pioglitazone yielded similar improvements in markers of IR whereas metformin did not affect IR. 20 The 3 agents induced comparable reductions in the free androgen index but none affected the lipid profi le.…”
Section: Orlistatmentioning
confidence: 97%
See 1 more Smart Citation
“…Dawson et al [91] recently reported that a weight-reducing therapy with the CB 1 antagonist rimonabant in obese women with PCOS resulted in a reduction of alanine aminotransferase, accompanied by a reduction of insulin resistance. In contrast, it has been reported that the amount of both vascular endothelial growth factor and interleukin-8, which play a crucial role in inflammation, are paradoxically increased upon rimonabant treatment of obese women with POCS, which may compensate the benefit associated with weight loss [98].…”
Section: The Ecs In Gynecological Disorders and Cancermentioning
confidence: 99%
“…These include fertility disorders like polycystic ovary syndrome (PCOS), endometriosis, and gynecological cancers [91-93]. …”
Section: The Ecs In Gynecological Disorders and Cancermentioning
confidence: 99%